Precipitation behaviour of single and duplex aged metastable β-Ti alloy, Ti–5Al–5Mo–5V–3Cr. Issue 14 (22nd September 2022) - Sharma, Deepak; Parfitt, David; Roebuck, Bryan; Kada, Sitarama Raju; Fabijanic, Daniel; Fitzpatrick, Michael E.
Abstract : This work presents the influence of single-aging and duplex-aging treatments on microstructure evolution and the associated properties of Ti-5553 β-Ti alloy. We found that single-aged samples with a slow heating rate and duplex-aged samples produced approximately the same microstructures and microhardness at all aging conditions. This can be attributed to the same precipitation mechanism in both cases as observed via in situ electrical resistivity measurements. The slowly heated and duplex-aged samples generally produced higher microhardness in comparison to fast-heated samples; however, the difference in the microhardness tended to decrease with aging time at higher temperatures. A correlation ( H v = 252 + 1790 / √ d ) between the microhardness values and the width of α-phase ( d ) was established for all the aged samples. Highlights Duplex aging and slow heating yield similar microstructure and microhardness. Duplex aging and slow heating showed similar precipitation mechanism. Duplex aging and slow heating generally produced higher hardness than fast heating. The gap in hardness for different aged conditions decreased at higher temperatures. The microhardness values showed a good correlation with the width of α-phase. GRAPHICAL ABSTRACT: UF0001